Impact of Proinflammatory Cytokines on the Virulence of Uropathogenic Escherichia coli - Engelsöy, Ulrik; Rangel, Ignacio; Demirel, Isak (Frontiers in Microbiology, 2019)
The effect of a urinary tract infection on the host is a well-studied research field. However, how the host immune response affects uropathogenic Escherichia coli (CFT073) virulence is less studied. The aim of the present study was to investigate the impact of proinflammatory cytokine exposure on the virulence of uropathogenic Escherichia coli. We found that all tested proinflammatory cytokines (TNF-α, IL-1β, IL-6, IL-8 and IFN-γ) induced an increased CFT073 growth. We also found that biofilm formation and hemolytic activity was reduced in the presence of all proinflammatory cytokines. However, a reduction in siderophore release was only observed in the presence of IL-1β, IL-6 and IL-8. Real time-qPCR showed that all proinflammatory cytokines except TNF-α significantly increased genes associated with the iron acquisition system in CFT073. We also found that the proinflammatory cytokines induced significant changes in type-1 fimbriae, P-fimbriae and gluconeogenetic genes. Furthermore, we also showed, using a C. elegans killing assay that all cytokines decreased the survival of C. elegans worms significantly. Taken together, our findings show that proinflammatory cytokines have the ability to alter the virulence traits of UPEC.